(untitled) (International Journal of Physiotherapy, 2021)
Background: HIV can lead to a plethora of health-related complications, such as cardiovascular and gait deficiencies. Some of the HIV obstacles are related among individuals; however, various facets come into play when considering and designing interventions for this population, like gender profile. This study aim to interpret the impact of HIV on distinct individuals; the present inquiry proposes to inspect the cardio-motor tendency on male versus female in Hispanics-Latinx living with HIV. Methods: Cardio-motor data was gathered from members’ records enrolled in La Perla de Gran Precio HIV Community Center in Puerto Rico. Results: The data analyzed in this examination were compiled from 262 participants, further allocated into 190 for the males and 72 for the females. Both groups were similar in age and CD4 count. An ANOVA comparison indicated variations in the male group with an increase (P<0.05) in heart rate frequency, SBP after the cardiovascular evaluation, and prolonged duration during the treadmill test distinguished the female group. The female group displayed distinct motor components with a considerable (P < 0.05) reduction in gait velocity, and treadmill inclination pertained to the male counterpart. Conclusion: Hispanic Latino living with HIV displayed a distinctive cardio-motor profile applied to gender. We encourage healthcare providers to incorporate the specific cardio-motor items alluded to in this investigation to identify the cardiovascular system and gait process that further alters the quality of life in those with HIV.